Phytosociological Studie Vegetation Ladakh Desert - Durani, P K; Singh, Gurucharan; Kachroo, P (Annals of Arid Zone, 2016)
The present paper annalyses the vegetational changes from temperate to arid climate along 350 km long tract from Sonamarg to Lah in Jammu and Kashmir State. Data from seven sites indicate tho reduction in vegetational cover and number of species towards xeric valleys of Leh. The woody species which are predominant on Kashmir side of the tract dlsappear and mesophytic herbs are replaced by tufted low herbs with massive rootstocks on Ladakh side.